Religion within the boundaries of mere reason : and other writings - Kant, Immanuel, 1724-1804, (Cambridge texts in the history of philosophy., 2018)
Religion within the Boundaries of Mere Reason is a key element of the system of philosophy which Kant introduced with his Critique of Pure Reason, and a work of major importance in the history of Western religious thought. It represents a great philosopher's attempt to spell out the form and content of a type of religion that would be grounded in moral reason and would meet the needs of ethical life. It includes sharply critical and boldly constructive discussions on topics not often treated by philosophers, including such traditional theological concepts as original sin and the salvation or 'justification' of a sinner, and the idea of the proper role of a church. This new edition includes slightly revised translations, a revised introduction with expanded discussion of certain key themes in the work, and up-to-date guidance on further reading.